2022
DOI: 10.2147/idr.s367510
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profiles, Antimicrobial Susceptibility Patterns, and Associated Factors in Patients Undergoing Orthopedic Surgery with Suspicion of Surgical Site Infection at Arba Minch General Hospital in Southern Ethiopia

Abstract: Background In the thoughts of all orthopedicians, the emergence of drug-resistant and biofilm-forming bacterial infections at orthopedic surgical sites is the most feared problem. Thus, this study aimed to determine the bacteriological profiles, antimicrobial susceptibility patterns, and biofilm forming ability of isolates, as well as factors associated with orthopedic surgical site infections (OSSIs). Methods An institution-based cross-sectional study was conducted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Among the GPC, all the isolates of S. aureus and cogulase negative S. aureus are sensitive to vancomycin with MIC <1. The pattern of susceptibility of E. faecalis is found to be 100% susceptibility for penicillin, ampicillin, linezolid vancomycin, and high-level gentamicin well correlating with studies of Alelign et al, 20 where all 33% of enterococcus isolated showed 100% vancomycin susceptibility. 3 In the present study, the total biofilm production tested by tube method is 54% biofilm producers and 46% non-biofilm producers.…”
Section: Discussionsupporting
confidence: 85%
“…Among the GPC, all the isolates of S. aureus and cogulase negative S. aureus are sensitive to vancomycin with MIC <1. The pattern of susceptibility of E. faecalis is found to be 100% susceptibility for penicillin, ampicillin, linezolid vancomycin, and high-level gentamicin well correlating with studies of Alelign et al, 20 where all 33% of enterococcus isolated showed 100% vancomycin susceptibility. 3 In the present study, the total biofilm production tested by tube method is 54% biofilm producers and 46% non-biofilm producers.…”
Section: Discussionsupporting
confidence: 85%
“…Alelign et al reported interesting data on “Bacteriological Profiles, Antimicrobial Susceptibility Patterns, and Associated Factors in Patients Undergoing Orthopaedic Surgery with Suspicion of Surgical Site Infection at Arba Minch General Hospital in Southern Ethiopia.” 1 We appreciate the efforts taken to investigate thoroughly the Multidrug-resistant [MDR] bacterial profile in orthopedic surgical site infections (OSSIs). Globally infections caused by MDR organisms are a significant cause of treatment failure and dissemination in hospitals and community settings.…”
Section: Dear Editormentioning
confidence: 99%
“…Different studies showed that Staphylococcus aureus accounts for 20-30% of infections whereas the coagulase-negative Staphylococci are responsible for approximately 20-40% of surgical implant infections. Other less frequent microbes identified in the orthopaedic implant-associated infections include the Gram-positive cocci, such as Streptococci and Enterococci, as well as Gram-negative bacilli, for example Pseudomonas aeruginosa and the Enterobacteriaceae family [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%